Effects of centrifugal buoyancy on developing convective laminar flow in a square channel occupied with a high porosity fibrous medium. (March 2015) - Alhusseny, Ahmed; Turan, Ali
Abstract: The development of three-dimensional heat transfer and fluid flow in a square channel rotating in a parallel-mode has been investigated numerically. The duct is occupied by a foam material of high porosity ( ɛ ⩾ 0.9) and subjected to a uniform wall heat flux. In regards to the influence of rotation, both the centrifugal buoyancy effect and Coriolis forces are considered in the current study. The generalised model is used to mathematically simulate the momentum equations employing the Boussinesq approximation for the density variation. Moreover, both the fluid and solid phases are considered to be in local thermal non-equilibrium. The governing equations are discretised according to the finite volume method employing the hybrid differencing scheme to calculate the fluxes across the faces of each control volume in the transverse plane. Computations are performed for a wide range of dimensionless parameters including the medium porosity (0.9 ⩽ ε ⩽ 0.97), rotation number (0 ⩽ Ro ⩽ 1.0), Darcy–Rayleigh rotational number (1.1 × 10 3 ⩽ Ra Ω ∗ ⩽ 6.2 × 10 5 ), and solid to fluid-phase thermal conductivity ratio (10 2 ⩽ κ ⩽ 10 3 ), while the values of Reynolds and Prandtl numbers are maintained constant at Re = 2000 and Pr = 0.7, respectively. The results reveal that the rotation seems to have a dominant role in enhancing heat transfer at high levels of porosity and low conductivity ratios. However, this role is reduced gradually with decreasing the medium porosity or increasing thermal conductivity ratio, but does not completely vanish. Eventually, the worth of using high porosity fibrous media in enhancing the heat transported through rotating channels has been inspected. An overall enhancement parameter was compared for the current study with a previous work regarding turbulent flow in a rotating clear channel, where it has been confirmed that the current proposal is practically justified and efficient.